2018
DOI: 10.1098/rsta.2017.0391
|View full text |Cite
|
Sign up to set email alerts
|

Nature of the high-speed rupture of the two-dimensional Burridge–Knopoff model of earthquakes

Abstract: The nature of the high-speed rupture or the main shock of the Burridge-Knopoff spring-block model in two dimensions obeying the rate-and-state dependent friction law is studied by means of extensive computer simulations. It is found that the rupture propagation in larger events is highly anisotropic and irregular in shape on longer length scales, although the model is completely uniform and the rupture-propagation velocity is kept constant everywhere at the rupture front. The manner of the rupture propagation … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 59 publications
0
6
0
Order By: Relevance
“…The mechanism of rupture and rebinding are different in stochastic simulation and MF equations. In the stochastic simulations, a rebinding event follows a rupture event in a single simulation run, while in the MF formalism, rupture and rebinding terms occur together (equation (12). Consequently, for bonds with n near the rupture front at the steady state, q n fluctuates between 1 and 0 in the former (for each simulation run), while in MF, á ñ q n varies continuously from 1 to the steady state value.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The mechanism of rupture and rebinding are different in stochastic simulation and MF equations. In the stochastic simulations, a rebinding event follows a rupture event in a single simulation run, while in the MF formalism, rupture and rebinding terms occur together (equation (12). Consequently, for bonds with n near the rupture front at the steady state, q n fluctuates between 1 and 0 in the former (for each simulation run), while in MF, á ñ q n varies continuously from 1 to the steady state value.…”
Section: Resultsmentioning
confidence: 99%
“…Steady states are an integral part of the stick-slip phenomena, and we focus on those instances at low deformation forces, which do not lead to material failure; in other words, the material sticks to a rest state. Most of the stick-slip studies focus on its dynamics, for instance, in earthquake models [9][10][11][12], the transition from static to dynamic friction [5], nanomanipulation [76], biology [13,62,63], deformation experiments on biocomposites [21][22][23][24], and designing hierarchical structures [44,45]. Our generic result represents a solution of the stick state that prevents material failure.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In [37], the two-dimensional Burridge-Knopoff model is simulated with a realistic rate and state friction law, in an attempt to reproduce the properties of large earthquakes. Particularly, the anisotropic characteristics of large avalanches are described.…”
Section: Discussionmentioning
confidence: 99%
“…The question here is to find the optimal time and length scale over which activity data are necessary to unambiguously determine a weak region in the system. As opposed to [37], a weak region in this model is not dynamically generated but is embedded in the relative strength of the parts of the system, effectively creating an asperity-like structure. It was found that given a rate of earthquake events, there exists an optimal scale up to which the spatial variations in the b-value and thereby the spatial variations of the stress profile can be determined within a limited error range.…”
Section: Discussionmentioning
confidence: 99%